No additive effect of fibrin sealants to tranexamic acid in perioperative blood conservation in total knee arthroplasty - Goderecci, Remo; Aloisi, Giuseppe; Caschera, Giovanni Giorgio; Paglia, Alessandro; Petralia, Giuseppe; Gagliardi, Luca; Saracco, Michela; Necozione, Stefano; Logroscino, Giandomenico (Acta Biomedica Atenei Parmensis, 2025)
Background: Total knee arthroplasty (TKA) is associated with significant blood loss and reducing allogenic blood transfusions remains a challenge for the orthopedic surgeons. Between the various methods of blood conservation, the most appropriate solution is to reduce the loss of blood during and after surgery.Materials and methods: This prospective, randomized, standard treatment-controlled trial is based on the evaluation of the hemostatic efficacy of fibrin tissue sealant in association with tranexamic acid (TXA) in patients undergoing TKA.Sixty patients were scheduled to receive a TKA and randomly divided into two groups: a control group (30 patients), in which the standard means of hemostasis were applied, including the intraoperative intravenous administration of 1 g of TXA, and a treatment group (30 patients), in which the same standard method to control bleeding was used and, in addition to the TXA administration, a fibrin tissue adhesive was sprayed locally during the operation.Results: The main outcome of the study was the evaluation of postoperative levels of hemoglobin (Hb), red blood cells (RBC), and hematocrit (Ht) at 3 hours and on the first, the third and the sixth days after surgery. We found a slight decrease in Hb, RBC and Ht levels in the treatment group, but the difference was not statistically significant. The recovery of the knee range of motion on the first and the third postoperative day was lower in the treatment group compared although also this difference was not significant. No substantial difference in the grade of postoperative pain was recorded. In no case allogenic blood transfusions were necessary. No major adverse events were registered in our series.Conclusions: The use of fibrin sealant (FS) did not produce significant benefits compared to the isolated use of TXA.